The effect of Professional Ethics, Auditor Experience, and Auditor Independence on Auditor Performance with Auditor Professional Skepticism as a Mediating Variable - Tika Dwi Permata Sari (AKUNTANSI DEWANTARA, 2022)
This research aims to determine the effect of professional ethics, experience, and auditor independence on auditor performance with auditor professional skepticism as a mediating variable at the Malang City Public Accountant Office registered with the Financial Services Authority. This type of research is quantitative research with a causal approach. While the source of data from this research was obtained from the results of distributing questionnaires at the Public Accountant Office in Malang City. The questionnaire was measured using a five-point Likert scale rated from strongly agree to strongly disagree. The sampling method used purposive sampling by determining specific criteria in sampling. The data analysis method used is path analysis. The results of the research prove that professional skepticism of auditors mediates the experience and independence of auditors so that they can have a significant and positive effect on the performance of auditors in Public Accounting Firms in Malang City. This shows that the better the experience and independence, the better the auditor's performance indirectly mediated by the auditor's professional skepticism.